(untitled) (Sociología y tecnociencia, 2026)
Population density and lower class marginalization due to the development of elite areas have alienated a community over its identity. The driving actors behind every social change exist, and they utilize a change through the villagers’ literacy power. Mainstreaming views on the actors’ active roles in social change essentially impact knowledge in the sociology of ethnic and cultural society. This study aims to describe the hidden actors behind the phenomenon of cultural movements that exist and develop national and international relations. This paper applies qualitative data collected in a participatory manner through interviews with key actors in Kampung Cempluk Festival. Focus group discussions were conducted with actors involved in every festival held by the community. Informants selected by snowball were then interviewed about their perceptions, motivations, and a value embodiment process. Researchers did the literature study through writings, releases, newspapers, mass media opinions, and several previous researches. The results indicate that alienation will foster citizens’ critical awareness of development and cultural values impacts. It is supported by driving actors who can read the potentials and opportunities in society. Thus, this research becomes the basis for policymakers in planning development which should prioritize a cultural approach and consider the threat of hidden power loss in society.